Understanding the Duties and Responsibilities of the Police in Criminal Cases in the Jurisdiction of a Country: A Study of Legal Literacy - Sardjana Orba Manullang (LEGAL BRIEF, 2022)
This study discussed the duties and roles of the legal apparatus, especially the Police, in handling criminal cases and courts against perpetrators of criminal acts. We manage this study with a phenomenological approach that we design in a qualitative study and rely on secondary data, namely data in the form of scientific evidence that has been published in several literature sources, books, and scientific papers of academic work that were released between 2010 and 2022. As for the mechanism of our study, we carried out extensive data coding techniques, thorough evaluations, and data interpretation to obtain findings that would answer the problems and hypotheses of this study with the principles of high validity and reliability. From the results of the study and discussion of the findings, we can conclude, among other things, that the duties of the Police are based on Article 13 of Law no. 2 of 2002 that the Police are law enforcement, citizen protection, and community service. Meanwhile, the understanding of jurisdiction is an authority possessed by the Police in forcing citizens to obey the criminal Law to uphold justice for the power and authority of state law towards citizens and other aspects. Thus, these findings are intended to be an additional important input for understanding legal and Police studies in future studies.